2007
DOI: 10.1038/sj.gt.3302938
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated viral gene transfer of transforming growth factor-β1 to human mesenchymal stem cells improves cartilage repair

Abstract: Bone marrow cells are routinely accessed clinically for cartilage repair. This study was performed to determine whether adeno-associated virus (AAV) effectively transduces human bone marrow-derived mesenchymal stem cells (hMSC) in vitro, whether AAV infection interferes with hMSC chondrogenesis and whether AAV-transforming growth factor-beta-1 (TGF-b1)-transduced hMSC can improve cartilage repair in vivo. Adult hMSC were transduced with AAVgreen fluorescent protein (GFP) or AAV-transforming growth factor b1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 43 publications
5
144
1
Order By: Relevance
“…Guo et al 32 reported similar results in a rabbit model of full-thickness cartilage defects using an ex vivo approach and a chitosan scaffold. Another study by Pagnotto et al 33 showed improved cartilage repair in osteochondral defects implanted with MSCs transduced with adeno-associated virus (AAV) carrying cDNA for TGF-b1. In their study, transgene expression slowly decreased from 100% at 2 weeks to 17% at 12 weeks, but it proved that gene therapy enables sustained delivery of the bioactive molecules for a period of time that is sufficient to induce and govern cellular response within the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al 32 reported similar results in a rabbit model of full-thickness cartilage defects using an ex vivo approach and a chitosan scaffold. Another study by Pagnotto et al 33 showed improved cartilage repair in osteochondral defects implanted with MSCs transduced with adeno-associated virus (AAV) carrying cDNA for TGF-b1. In their study, transgene expression slowly decreased from 100% at 2 weeks to 17% at 12 weeks, but it proved that gene therapy enables sustained delivery of the bioactive molecules for a period of time that is sufficient to induce and govern cellular response within the defect.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, AAV was used to transfer TGF-b 1 cDNA into human MSCs, which were subsequently implanted into osteochondral defects in nude rats. 41 Healing was superior to that achieved with negative control GFP cDNA. It was noted that, by 12 weeks only 12% of the cells within the defect were GFP + .…”
Section: Advances In Bone Healingmentioning
confidence: 87%
“…More than 50 adenovirus serotypes are available for gene therapy and serotype 5 (Ad5) has been the mostly used in both in vitro and in vivo studies. Adenovirus is used to transfer GF genes (TGF-β, FGF-2, IGF-1, BMPs and Growth and differentiation factor 5, GDF-5) into cells [8,20,25,[40][41][42][43][44][45][46][47][48][49]. Genes, in encapsuled viral [24] vector, can be injected directly in vivo [50,51] or through decalcified cortical bone matrix (DCBM) as scaffold that contains the viral particles [52].…”
Section: Viral Vectormentioning
confidence: 99%